Growth of carrot cultivars in different environments - Pereira, Gustavo Antônio Mendes; Oliveira, Maxwel Coura; Braga, Renan Rodrigues; Silva, Daniel Valadão; Oliveira, Altino Júnior Mendes; Fernandes, José Sebastião Cunha; Andrade Júnior, Valter Carvalho de (Federal University of Piauí, 2015)
The carrot (Daucus carota) is the fifth most widely grown vegetable crop in Brazil, with an average yield of only 32.1 t ha-1 with productive potential to reach 80 t ha-1. One reason cited for this low productivity is planting varieties not adapted to the environments found in Brazil. Knowing the importance of genotype and environment interaction, aimed to evaluate the growth of carrot cultivars in autumn-winter crop in two counties with different soil and climatic characteristics of the Upper Valley Jequitinhonha, MG. Six carrot cultivars (Brasilia, Nantes, Kuronan, Esplanade, Plateau and Tornado) were grown in two environments (Couto de Magalhães of Mines and Diamantina). Plants were sampled weekly and regression equations were adjusted from time. For plant height set to linear Couto de Magalhães de Diamantina Minas and quadratic models, as in root length models the behavior was reversed. This difference shows that different environments alter the pattern of growth. The distinct environments resulted in different behaviors of cultivars of carrot, and in Couto de Magalhães de Minas productivity was higher. Regardless of the growing environment to Nantes variety showed lower productivity. The Plateau cultivar is best suited for planting in the Diamantina and Kuronan and Plateau to Couto Magalhães de Minas.